REFUSAL STRATEGIES REALIZED BY PROFICIENT EFL STUDENTS - Eviliana and Tiur Simanjuntak (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2011)
This research was aimed at describing the strategies of proficient  EFL (English as a Foreign Language) students’ refusal realization in English. This research employed Qualitative research method. The subjects were 18 EFL students of English Study Program Sriwijaya University whose TOEFL prediction scores were 450 above. DCT was used as the instrument of collecting data. Data were analyzed based on combined refusal classification by Wannaruk (2005) and Campillo (2009). The results of this research show that  proficient EFL students mostly used the indirect strategies in their refusal realization in English. There were 318 (64%) of the 494 semantic unit in proficient EFL English refusal that were categorized into indirect strategy. There were 42 (9%) of the 494 semantic units in proficient EFL students’ English refusal that were categorized into direct strategy. There were 105 (22%) semantic formula of the 494 semantic formula in proficient EFL students’ English refusal were categorized into adjunct to refusals.